Diversidade genética e patogenicidade de Harknessia pseudohawaiiesis Crous & Carnegie, Apoharknessia eucalyptorum Crous & Lee E Chalara holubovae Koukol A Eucalyptus benthamii Maiden et Cambage - Moro, Michele (2021)
In plantations of elcalyptus spp. the occurrence of phytopathogens that induce the symptom of leaf spot is considered frequent. An example is Apoharknessia spp. and Harknessia spp. that in recent years have aroused much interest, because they are new in certain locations, or even because they have not been described, leaving gaps from the phytopathological point of view, because their pathogenicity, symptomatology, potential damage and impacts have not been studied in depth. Given the need to complete theknowledge about the phytopathogenic microorganism as well as the interactions that result in the disease process, the present work seeks to perform phenotypic analysis of severity and pathogenicity of isolates of A. eucalypturum and Harknessia spp. on clones of E. benthamii. The work was conducted at the UNICENTRO nursery in Irati-Pr, where six fungal isolates were inoculated on two leaves of E. benthamii clonal seedlings, which were evaluated for severity at 7 days after inoculation (DAI) and 14 DAI with 277 and 284 days of age respectively. The fungi used in the work were identified and compared with the sequences deposited at the NCBI (National Center for Biotechnology Information) and later phylogenetic analysis was done through dendrograms. Phenotypic variability was observed regarding the aggressiveness of four isolates of A. eucalyptorum, one isolate of Harknessia pseudohawaensis and one isolate of Chalara holubovae to clonal seedlings of E. benthamii. Harknessia and Apoharknessia species were separated into distinct clusters, confirming that the species are genetically different, with 100% dissimilarity, indicating genetic diversity in the isolates evaluated. It is noteworthy that a A. eucalyptorum showed interesting genetic variability because the isolates came from the same geographical region. The better understanding of this variability is vital for future strategies to manage the disease. This is the first report of pathogenicity of H. pseudohawaiensis and C. holubovae to E. benthamii, thus describing a new list of pathogens for the species.